Context‐dependent transcriptional regulation of microglial proliferation - Belhocine, Sarah; Machado Xavier, André; Distéfano‐Gagné, Félix; Fiola, Stéphanie; Rivest, Serge; Gosselin, David (Glia, 2022)
Microglia proliferate during brain development and brain lesions, but how this is coordinated at the transcriptional level is not well understood. Here, we investigated fundamental aspects of the transcriptional process associated with proliferation of mouse microglia during postnatal development and in adults in a model of induced microglial depletion‐repopulation. While each proliferative subset displayed globally a distinct signature of gene expression, they also co‐expressed a subgroup of 1370 genes at higher levels than quiescent microglia. Expression of these may be coordinated by one of two mechanisms of regulation with distinct properties. A first mechanism augments expression of genes already expressed in quiescent microglia and is subject to regulation by Klf/Sp, Nfy, and Ets transcription factors. Alternatively, a second mechanism enables de novo transcription of cell cycle genes and requires additional regulatory input from Lin54 and E2f transcription factors. Of note, transcriptional upregulation of E2f1 and E2f2 family members may represent a critical regulatory checkpoint to enable microglia to achieve efficient cell cycling. Furthermore, analysis of the activity profile of the repertoire of promoter‐distal genomic regulatory elements suggests a relatively restricted role for these elements in coordinating cell cycle gene expression in microglia. Overall, proliferating microglia integrates regulation of cell cycle gene expression with their broader, context‐dependent, transcriptional landscape. Main Points Overall gene signature of proliferating microglia is coupled to brain context. Distinct combinations of transcription factors coordinate induction of cell cycle genes. Induction of E2f family members may represent a checkpoint for microglial cell cycle.